Frekuensi Nafas dan Pulsus Ular Sanca Batik (Malayopython reticulatus) Lokalitas Jawa - Raharjo, Slamet; Hartati, Sri; Indarjulianto, Soedarmanto; Widayanti, Rini (Jurnal Sain Veteriner, 2018)
Reticulated python (Malayopython reticulatus) java locality is highly demand as pet animal. Respiratory and pulse rate were important physiological data needed for diagnostic references. The aim of this research was to study the repiratory and pulse rate on Java M. reticulatus. Thirthy healthy adult Java M. reticulatus were used in this study. The respiratory rate recorded by counting inspiratory and expiratory movement of the thorax for one minute and pulse rate recorded by heart palpation for one minute, measured at 6-8 AM and at 4-6 PM for five consecutive days. Temperature and humidity were record as secondary data. The data were analyzed using independent t-Test. The respiratory rate in this study recorded in the morning ranged 5-48 breaths/minute averaging 20 breaths/minute and in the evening ranged 7-49 breaths/minute averaging 24 breaths/minute. The pulse rate in the morning ranged 21-68 beats per minute (bpm) averaging 45.5 bpm and in the evening ranged 40-82 bpm averaging 56 bpm. Totally, M. reticulatus having the respiratory rate 5-49 breaths/minute and pulse rate 21-82 bpm. The morning temperature ranged 25-27oC and the evening 26-27.5oC. The range of morning and evening air humidity is 66-75% and 65-70% respectively. The results showed that the comparison of respiratory rate (R) and pulse rate (P) were in normal range namely 1:2.25 in the morning and 1:2.33 in the evening. There were no significant differences (P>0.05) between morning and evening respiratory rate and no significant effect (P>0.05) of temperature and humidity on respiratory and pulse rate. It could be concluded that healthy adult Java M. reticulatus has a respiratory rate 5-49 breaths/minute dan pulse rate 21-82 bpm.